2017
DOI: 10.1016/j.fluid.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of vapour-liquid equilibrium and density modelling of mixtures related to carbon capture and storage with the SRK, PR, PC-SAFT and SAFT-VR Mie equations of state for industrial uses

Abstract: Carbon capture and storage (CCS) is nowadays considered as one of the most promising methods to counterbalance the CO 2 emissions from the combustion of fossil fuels, natural gas processing, cement manufacturing, etc. In dealing with the transport and the storage of CO 2 -rich streams, design of a safe and optimum process requires the knowledge of thermophysical properties (especially density) of CO 2 -rich mixtures. Consequently, the development of accurate thermodynamic models to evaluate these properties pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 43 publications
0
32
0
2
Order By: Relevance
“…Furthermore, the % AARD‐EXP for the cubic EoS is similar to % AARD‐MC, while a higher difference is presented for PC‐SAFT. This higher variation of the % AARD value for PC‐SAFT is attributed to the VLE data at 244.26 K. The k ij parameters of PC‐SAFT EoS generally show higher sensitivity to the dataset used for the regression, compared to the respective ones of cubic EoS . However, similar sensitivity of the k ij parameters for the three EoS is shown when high temperature VLE GEMC simulation data are added.…”
Section: Resultsmentioning
confidence: 84%
“…Furthermore, the % AARD‐EXP for the cubic EoS is similar to % AARD‐MC, while a higher difference is presented for PC‐SAFT. This higher variation of the % AARD value for PC‐SAFT is attributed to the VLE data at 244.26 K. The k ij parameters of PC‐SAFT EoS generally show higher sensitivity to the dataset used for the regression, compared to the respective ones of cubic EoS . However, similar sensitivity of the k ij parameters for the three EoS is shown when high temperature VLE GEMC simulation data are added.…”
Section: Resultsmentioning
confidence: 84%
“…This study relied on 22,904, 26,479, and 31,928 measurements of VLE, binary mixture density, and single-phase density, respectively. Perez et al (2017) concluded that SAFT EoSs methods for predicting density had accuracies better than 3.0% AAD% (Percent Absolute Average Deviation) for all chemical systems studied, and an average AAD% of 1.16. All data taken together, the SAFT EoS was superior to other EoS methods studied.…”
Section: Resultsmentioning
confidence: 98%
“…), знание которых необходимо для рационального проектирования разработки га зовых и газоконденсатных месторождений, а так же в технологических процессах при транспорти ровке и переработке добываемого сырья. В работе [2] .…”
Section: уравнение состояния пенга-робинсона и его модификацияunclassified
“…Основной подход к определению коэффициента сверхсжимаемости углеводородных смесей осно ван на использовании уравнения состояния. Нес мотря на то, что большинство уравнений состоя ния было предложено еще в XX в., их сравнитель ный анализ и модификация продолжается и по сей день [2,3]. Следует отметить, что практически все уравнения являются эмпирическими связями, ко торые требуют точной «настройки» коэффициен тов парного взаимодействия между парами углево дородов, что не всегда возможно реализовать в условиях недостатка экспериментальных данных.…”
unclassified